A Fuzzy Goal Programming Approach to Multiobjective Transportation Problems. Issue 2 (2nd April 2020) - Rivaz, S.; Nasseri, S. H.; Ziaseraji, M.
Abstract : The current paper focuses on a multiobjective transportation problem which is a special type of vector minimum problem. In order to deal with such a problem, a new model based on fuzzy goal programming is suggested. Different solutions are obtained according to the priorities of the decision maker in the proposed model. With respect to its properties, at least a weakly efficient solution is yielded by solving the new model. To demonstrate the validity and strengths of the suggested model, some numerical examples are given. Further, a comparison is made with different existing methods.